ABJADPEDIA INOVASI MENGATASI PROBLEM KESULITAN MENULIS (DYSGRAPHIA) DI PANTI YAUMA 19 SURABAYA - Simanjuntak, Dinar Ester; Yudhoyono, Ahmad Yusuf; Abhista, Muhammad Andea; Novianti, Dinda Cahya; Cahya , Dimas Maulana Eka (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
Writing is a skill needed in everyday life that is useful for expressing something in written form. Dysgraphia is a disorder experienced by an individual who has difficulty expressing things in written language. Yauma Home is one of the orphanages where some of the foster children experience writing difficulties (dysgraphia). In its solution, the PKM-PM team used Abjadpedia media to deal with the problem of writing difficulties that existed at the orphanage. Abjadpedia media can train motor skills in children with dysgraphia. The Abjadpedia team divides activities into preparation stages, activity implementation, evaluation and program sustainability. The number of children who were exposed to the application of Abjadpedia media in order to solve writing problems at Panti Yauma 19 Surabaya was 10 children. At the end of the meeting, there were visible changes in the children's writing skills which had begun to improve.